Development of novel optically active two-canter phase-transfer catalysts for enantioselective synthesis of -amino acid - Shibatomi, Kazutaka; Kobayashi, Fumito; Tsuzuki, Yuya; Iwasa, Seiji (Vietnam Journal of Chemistry, 2014)
New optically active bis-quaternary ammonium salts were synthesized and applied to catalytic asymmtric alkylation of tert-butyl glycinate benzophenone Schiff base to provide a chiral a-amino acid derivative with 54% ee.